Historia médica: su potencialidad en la gestión de costos hospitalarios (2019)
This study aims to identify the potentialities of medical history as a source of data needed to obtain cost information, information of valuable importance for hospital management. As far as design is concerned, it is a mixed-source research: field and documentary re-search, with descriptive scope. The interview was used as a technique for carrying out the research and the interview guide was used as an instrument. In addition, a documentary review and articulation of theories with empirical evidence was carried out. It was found that the medical history or health record contains, among other aspects, the list of acts and medical procedures performed during the stay of a patient in the hospital, acts and medical procedures likely to generate costs. Among the potentialities of medical history is that it is a tool that allows the knowledge of cost elements gener-ated in the care of patients. In this sense, the medical history is linked to the information system, being useful for hospital management and cost control. It is concluded that the medical history generates data susceptible to feed the information system for the management of hospital costs, in order to provide quality services to patients and optimization of management.